The Effect of embossing roll roughness and forming temperature on damage to menthol-coated aluminum foil on packaging - Ludfi Setiawan; Asrori Asrori (Jurnal POLIMESIN, 2023)
The Aims of this study are to determine  the effect of embossing roll roughness and forming temperature on the damage of menthol-coated aluminum foil on the packaging, and to determine the best temperature and embossing roll roughness on the quality of the menthol coating on the packaging. In this study, the independent variables were embossed roll wave (roughness level 1000,500.0 µm) and menthol foil temperature (22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46 °C) to be manipulated, observed, and measured to know the effect with the dependent variable. And because the established variable is the quantity of broken menthol foil packaging that is measured via way of means of calculating the share of period of menthol foil packaging this is torn as compared to the whole period of the foil. Based on the effects of the discussion, it can be concluded that the forming temperature and the embossing roll roughness affect the damage to the menthol packaging layer. In the ANOVA follow-up test, the lowest and best mean value for the forming temperature is at T12 or 44°C, not at T13 or 46°C because at these temperatures the menthol layer on the package is too hot and starts to damage the coating and the lowest and best average for the roughness level of embossed rolls is at E3 with a roughness value of 0 µm (fine).